Kesehatan Otak pada Anak Usia 24–36 Bulan: - Sofia, Norlaila; Zubaidah, Tien; Rusmilawaty, Rusmilawaty (Jurnal Skala Kesehatan, 2025)
Implementation of Evidence-Based Midwifery and Environmental Health Impact on Brain Health of Children Aged 24–36 Months. This study aims to analyze the effect of environmental quality on brain health of children aged 24–36 months through an evidence-based midwifery approach. A cross-sectional design was used with 40 mother–child pairs from Astambul Public Health Center. Data were collected via interviews, observation, anthropometric measurement, and developmental screening using the KPSP questionnaire. Data were analyzed using Chi-square and odds ratio. The findings revealed that housing quality did not significantly affect child growth (p=0.498) but had a highly significant relationship with child development (p=0.004; OR=1.93). There was also a near-significant association between housing quality and brain health (p=0.056; OR=4.60) at 95% confidence level (a=0.05) . These results highlight the importance of a supportive living environment for optimal brain development in early childhood. The study recommends integrating evidence-based midwifery with environmental health interventions to optimize early childhood growth and development.